STRATEGI PEMASARAN TANAMAN TOMAT ( Salonum lycopersicum) DI KEBUN PRAKTEK FAKULTAS TEKNOLOGI PANGAN PERTANIAN DAN PERIKANAN - Taras Iawan Saputera Wanda; Margareta Olivia Wilma Tokan; Yohana Anggriani (Universitas Cokroaminoto Palopo, 2026)
This study aims to determine the tomato marketing strategy in the Practical Garden of the Faculty of Food Technology, Agriculture, and Fisheries, Nusa Nipa University, Maumere. The respondents were selected using a purposive sampling technique. Respondents were tomato farmers and tomato consumers. Data analysis used a SWOT analysis. The internal factors (strengths and weaknesses) scored 3.20, indicating that the internal conditions of tomato marketing are strong, meaning that strengths outweigh weaknesses. Given these internal conditions, tomato marketing has the potential to be developed and lead to business growth. The external factors (opportunities and threats) scored 2.98, indicating that the external conditions of tomato marketing are moderate, meaning that available opportunities outweigh threats. This situation provides an opportunity for continued development of tomato marketing, thus supporting the growth of the tomato marketing business. A viable marketing strategy is a growth strategy with a stability approach, which leverages existing strengths and opportunities, improves weaknesses, and anticipates threats gradually and sustainably by leveraging farmer experience and production continuity, improving tomato quality, maximizing support from relevant institutions, and controlling and efficiencies in production and distribution costs. The implementation of this strategy is expected to increase the sustainability of tomato marketing in practical gardens